Interlimb asymmetries: Understanding how to calculate differences from bilateral and unilateral tests - Bishop, C.; Read, P.; Lake, J.; Chavda, S.; Turner, A. (Strength and Conditioning Journal, 2018)
Interlimb asymmetries have been a popular topic of investigation in the strength and conditioning literature. Recently, numerous equations have been highlighted that can quantify these between-limb differences. However, no distinction was provided on whether their use was applicable to both bilateral and unilateral tests. This article provides a framework for selecting the most appropriate asymmetry equation based on the selected test method, ensuring accurate calculation and interpretation. In addition, considerations for data analysis have also been included as a guide for practitioners on the relevance of monitoring interlimb differences longitudinally.